2019
DOI: 10.1097/md.0000000000014608
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of plakophilin 3 is associated with poor prognosis in ovarian cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In this study, we found that the expression of PKP3 mRNA and protein was upregulated in ovarian cancer and significantly correlated with PFS in patients with ovarian cancer. Qian et al showed that PKP3 was highly expressed in both cytoplasm and nucleus of ovarian cancer, which was consistent with our research, high expression of PKP3 was correlated with advanced FIGO stage, lymph node metastasis, and poor prognosis [ 13 ]. Lim et al .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this study, we found that the expression of PKP3 mRNA and protein was upregulated in ovarian cancer and significantly correlated with PFS in patients with ovarian cancer. Qian et al showed that PKP3 was highly expressed in both cytoplasm and nucleus of ovarian cancer, which was consistent with our research, high expression of PKP3 was correlated with advanced FIGO stage, lymph node metastasis, and poor prognosis [ 13 ]. Lim et al .…”
Section: Discussionsupporting
confidence: 91%
“…In terms of potential mechanism, PKP2 could regulate the activity of Wnt/β-catenin in colon cancer-associated fibroblasts [54], and PKP2 promoted the proliferation and migration of lung cancer by activating EGFR signaling pathway [38]. In addition, PKP3 regulated autophagy and invasion of ovarian cancer through MAPK/JNK/ERK1/2/mTOR signaling pathway [13,14]. GO and KEGG enrichment analysis suggested that PKP2/3 and their correlated genes were mainly involved in the formation of plasma membrane, collagen-containing extracellular matrix, cell-cell and anchoring junction.…”
Section: Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…PKP3 is a member of the arm repeat family of catenin proteins and serves as a structural component of desmosomes, mediating cell-cell adhesion and communication [ 21 ]. Recent studies have shown that PKP3 participates in the progression and metastasis of ovarian cancer, prostate cancer and nasopharyngeal carcinoma [ 22 24 ], but its molecular mechanism underlying the regulation of antitumor immunity remains unclear. We showed that PKP3 forms protein-RNA complexes with FXR1, which increases the mRNA stability of the deubiquitinase OTUB1.…”
Section: Introductionmentioning
confidence: 99%